Two digit number thistime by multiplying the sum of digits by eight and then subtracting five or so it is obtained by multiplying the differ

Question

Two digit number thistime by multiplying the sum of digits by eight and then subtracting five or so it is obtained by multiplying the difference of the digits by 16 and adding three find the number

in progress 0
Athena 4 weeks 2021-09-22T22:39:06+00:00 2 Answers 0 views 0

Answers ( )

    0
    2021-09-22T22:40:48+00:00

    Answer:

    Step-by-step explanation:

    Let the two digit number be 10x + y where x is the tens digit and y is the ones digit.

    Now, according to the question.

    10x + y = 8(x + y) – 5

    10x + y = 8x + 8y – 5

    10x – 8x + y – 8y = – 5

    2x – 7y = – 5  ……………..(1)

    And,

    10x + y = 16(x – y) + 3

    10x + y = 16x – 16y + 3

    10x – 16x + y + 16y = 3

    – 6x + 17y = 3  …………….(2)

    Now, multiplying the equation (1) by 17 and (2) by 7, we get

    34x – 119y = – 85 ……………(3)

    – 42x + 119y = 21 …………..(4)

    Now, adding (3) and (4), we get

      34x – 119y = – 85

    – 42x + 119y =   21

    _________________

     – 8x             = – 64

    _________________

    ⇒ 8x = 64

    x = 64/8

    x = 8 

    So, tens digit is 8.  

    Substituting the value of x = 8 in (1), we get

    2x – 7y = – 5

    2*8 – 7y = – 5

    16 – 7y = – 5

    – 7y = – 5 – 16

    – 7y = – 21

    7y = 21

    y = 21/7

    y = 3

    Ones digit is 3.

    So, the required number is 83.

    0
    2021-09-22T22:41:00+00:00

    Solution :

    Let the ten’s place digit be r & unit’s place digit be m.

    \boxed{\bf{Original\:number=10r+m}}}}

    A/q

    \underbrace{\bf{1_{st}\:Case\::}}}}

    \longrightarrow\sf{8(r+m)-5=10r+m}\\\\\longrightarrow\sf{8r+8m-5=10r+m}\\\\\longrightarrow\sf{8r-10r+8m-m=5}\\\\\longrightarrow\sf{-2r+7m=5....................(1)}

    \underbrace{\bf{2_{nd}\:Case\::}}}}

    \longrightarrow\sf{16(r-m)+3=10r+m}\\\\\longrightarrow\sf{16r-16m+3=10r+m}\\\\\longrightarrow\sf{16r-10r-16m-m=-3}\\\\\longrightarrow\sf{6r-17m=-3..........................(2)}

    \underline{\boldsymbol{Using\:Substitution\:method\::}}}

    From equation (2),we get;

    \longrightarrow\sf{6r-17m=-3}\\\\\longrightarrow\sf{6r=-3+17m}\\\\\longrightarrow\sf{r=-3+17m/6......................(3)}

    ∴ Putting the value of r in equation (1),we get;

    \longrightarrow\sf{-2\bigg(\dfrac{-3+17m}{6} \bigg)+7m=5}\\\\\\\longrightarrow\sf{\dfrac{6-34m}{6} +7m=5}\\\\\\\longrightarrow\sf{6-34m+42m=30}\\\\\longrightarrow\sf{6+8m=30}\\\\\longrightarrow\sf{8m=30-6}\\\\\longrightarrow\sf{8m=24}\\\\\longrightarrow\sf{m=\cancel{24/8}}\\\\\longrightarrow\bf{m=3}

    ∴ Putting the value of m in equation (3),we get;

    \longrightarrow\sf{r=\dfrac{-3+17(3)}{6} }\\\\\\\longrightarrow\sf{r=\dfrac{-3+51}{6} }\\\\\\\longrightarrow\sf{r=\cancel{\dfrac{48}{6} }}\\\\\longrightarrow\bf{r=8}

    Thus;

    \boxed{\sf{The\:number=10r+m=[10(8)+3]=[80+3]=\boxed{\bf{83}}}}}

Leave an answer

Browse
Browse

18:9+8+9*3-7:3-1*13 = ? ( )